2021
DOI: 10.21203/rs.3.rs-910460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Determinants of Under-nutrition Among Children Under Five Years of Age in Afar Region, Ethiopia: Evidence From 2016 Ethiopian Demographic and Health Survey

Abstract: BackgroundUndernutrition is one of the major public health concerns among infants and young children in the country. Childhood under-nutrition is widespread in low and middle-income countries. This study was initiated to assess the prevalence of under-nutrition and its associated factors among under-five children in Afar Region, Ethiopia. MethodsThe data for this study were extracted from the Ethiopian Demographic and Health Survey (EDHS) 2016. The information collected from 937 children born 5 years before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…This increase in wasting is an alarming increased risk of death for children. This study found the prevalence of stunting (19%) lower than previous studies conducted in Ethiopia that identi ed the prevalence of stunting as 21-47.9% (12,13,17,26). This may be because of variation in the study area.…”
Section: Discussioncontrasting
confidence: 83%
“…This increase in wasting is an alarming increased risk of death for children. This study found the prevalence of stunting (19%) lower than previous studies conducted in Ethiopia that identi ed the prevalence of stunting as 21-47.9% (12,13,17,26). This may be because of variation in the study area.…”
Section: Discussioncontrasting
confidence: 83%